Lipoprotein cholesteryl ester production, transfer, and output in vivo in humans - Schwartz, Charles C.; VandenBroek, Julie M.; Cooper, Patricia S. (Journal of lipid research, 2004)
Our aim was to identify and quantify the major in vivo pathways of lipoprotein cholesteryl ester transport in humans. Normal (n = 7), bile fistula (n = 5), and familial hypercholesterolemia (FH; n = 1) subjects were studied. Each received isotopic free cholesterol in HDL, LDL, or particulate form, along with another isotope of free or esterified cholesterol or mevalonic acid. VLDL, intermediate density lipoprotein (IDL), LDL, HDL, blood cells, and bile were collected for up to 6 days for analysis of radioactivity and mass of free and esterified cholesterol. These raw data were subjected to compartmental analysis using the SAAM program. Results in all groups corroborated net transport of free cholesterol to the liver from HDL, shown previously in fistula subjects. New findings revealed that 70% of ester was produced from free cholesterol in HDL and 30% from free cholesterol in LDL, IDL, and VLDL. No evidence was found for tissue-produced ester in plasma. There was net transfer of cholesteryl ester to VLDL and IDL from HDL and considerable exchange between LDL and HDL. Irreversible ester output was from VLDL, IDL, and LDL, but very little was from HDL, suggesting that selective and holoparticle uptakes of HDL ester are minor pathways in humans. It follows that 1) they contribute little to reverse transport, 2) very high HDL would not result from defects thereof, and 3) the clinical benefit of high HDL is likely explained by other mechanisms. Reverse transport in the subjects with bile fistula and FH was facilitated by ester output to the liver from VLDL plus IDL.